2017
DOI: 10.1016/j.drugalcdep.2017.01.043
|View full text |Cite
|
Sign up to set email alerts
|

Executive function fails to predict smoking outcomes in a clinical trial to motivate smokers to quit

Abstract: Background Executive function (EF) is considered an important mediator of health outcomes. It is hypothesized that those with better EF are more likely to succeed in turning their intentions into actual health behaviors. Prior studies indicate EF is associated with smoking cessation. Experimental and longitudinal studies, however, have yielded mixed results. Few studies have examined whether EF predicts post-treatment smoking behavior. Fewer still have done so prospectively in a large trial. We sought to deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 33 publications
0
6
1
Order By: Relevance
“…Brega et al [56] showed that older persons with impaired executive functioning were less likely to quit smoking than those with normal executive functioning. However, recent data did not confirm the relationship between executive cognitive dysfunction and smoking cessation [57]. Moreover, another study even showed that persons over 75 years of age who quit smoking had lower cognitive functioning than persons who continued smoking [58].…”
Section: Self-management Skillsmentioning
confidence: 94%
“…Brega et al [56] showed that older persons with impaired executive functioning were less likely to quit smoking than those with normal executive functioning. However, recent data did not confirm the relationship between executive cognitive dysfunction and smoking cessation [57]. Moreover, another study even showed that persons over 75 years of age who quit smoking had lower cognitive functioning than persons who continued smoking [58].…”
Section: Self-management Skillsmentioning
confidence: 94%
“…EFs have a key role in planning, sequencing and monitoring goal-directed thoughts, behaviours and emotions ( Allan et al, 2016 ; Hofmann, Schmeichel, & Baddeley, 2012 ; Razani, Boone, Lesser, & Weiss, 2004 ), and alteration of higher cognitive processes, for example, self-regulation and planning ( Fox et al, 2017 ), reduce the probability to achieve personal goals. In line with Meyers and colleagues (2015) , emotion processing and executive function decrements may interfere with an individual's ability to quit smoking ( Meyers et al, 2015 ).…”
Section: Assessing the Combined Effect Of Rumination And Ef Impairmenmentioning
confidence: 99%
“…Nevertheless, it is not clear how rumination and EF affect the adoption of the smoking behavior and/or the motivation to quit, as research conducted until now tends to be limited by methodological and theoretical shortcomings. Particularly, Fox and colleagues (2017) stressed the tendency to use different types of methodologies to assess EF, and for each of them to assess a specific component of EF for example, Wisconsin Card Sorting Test (set-shifting), Stroop Test (response inhibition), Go/No-go task (attention and set-shifting), Trail Making Test (visual attention), etc. with research often providing mixed results.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In the few studies that controlled for acute and/or withdrawal effects of nicotine on measures of self-regulation, smokers did not show deficits in Inhibition or Verbal Fluency, but they were more impulsive [9] and showed Planning difficulties [67], suggesting that performance on some, but not all hot abilities are more impaired in this population. Indeed, Fox et al [68] did not observe associations between smoking and cool executive functions, including Inhibition. Assuming that chronic smoking impairs hot more than cool cognitive abilities makes sense because the former are related to emotional/motivational responses that lead people to smoke and have difficulty quitting (e.g., [1416]).…”
Section: Introductionmentioning
confidence: 99%